An Attempt to Survive from Paralysis: Epiphanies in Dubliners - Golban, Petru; Ozturk, Goksel (Border Crossing, 2017)
Amid the complexity of concern of the modernist literary discourse in Britain, the thematic nucleus of James Joyce’s writings is formed by certain basic aspects of life, such as individuality, art, religion, nation, language, and his work shows the two hypostases of the author himself as accomplished artist and Irish citizen. In a troubled period in the history of Europe and of his own country, Joyce grasped the sense and the atmosphere of frustration, alienation, futility, chaos, and confusion. The concerns of Dubliners, his first important book, published in 1914, consist in rendering the political and social life of Dublin, the misery of human condition, the theme of exile, the problems of the individual’s existence in an urban background which Joyce saw as paralyzed and, like Eliot, as an expression of a period of crisis in the history of humanity. Joyce intended “to write a chapter of the moral history” of his country, and he chose Dublin as it seemed to him “the centre of paralysis” on different levels which he presented under four aspects: childhood, adolescence, maturity, and public life. All the fifteen stories of the book express life experiences of the characters that are of unpretentious standing, incapable to fulfil inner potentialities and to establish communication with others. At moments they experience relevant epiphanic realisations, seemingly due to some trivial incidents – by which they receive an apparent perspective of accomplishment – and though they attempt to escape the bonds of everyday life and of their trapping circle of existence, all they get is an acute sense of frustration, alienation, and entrapment. To reveal and compare the thematic status of the epiphany in the short stories with regard to various issues of individual existence and to the use of motifs and symbols that create an increasing complexity of ideas and subjective human reactions represents the main purpose and the essence of the content of the present study.